The researching of expiration date for substances of potassium 2-((4-amino-5-(morfolinometyl)-4H-1,2,4-triazole-3-yl)thio)acetate (PKR-173) by "accelerated aging" method - Shcherbyna, R. О.; Maletskyy, M. M.; Щербина, Роман Олександрович; Малецький, Микола Миколайович (Харків : НФаУ, 2020)
Modern pharmaceutical science is complex and massive structure, that is focused on the research and development of new effective and not toxic drugs. The process of creating drugs is very time-consuming and involves many stages of research, not only biological action but chemical and technological aspects. Thus, an important step in this direction is to study the expiration date of drug substances.